Interaction of Atmospheric-Pressure Air Microplasmas with Amino Acids as Fundamental Processes in Aqueous Solution. - Renwu Zhou; Rusen Zhou; Jinxing Zhuang; Zichao Zong; Xianhui Zhang; Dongping Liu; Kateryna Bazaka; Kostya Ostrikov (PLoS ONE, 2016)
Plasma medicine is a relatively new field that investigates potential applications of cold atmospheric-pressure plasmas in bioengineering, such as for bacterial inactivation and degradation of organic molecules in water. In order to enunciate mechanisms of bacterial inactivation at molecular or atomic levels, we investigated the interaction of atmospheric-pressure air microplasmas with amino acids in aqueous solution by using high-resolution mass spectrometry (HRMS). Results show that the oxidation effect of plasma-induced species on the side chains of the amino acids can be categorized into four types, namely hydroxylation, nitration, dehydrogenation and dimerization. In addition, relative activities of amino acids resulting from plasma treatment come in descending order as follows: sulfur-containing carbon-chain amino acids > aromatic amino acids > five-membered ring amino acids > basic carbon-chain amino acids. Since amino acids are building blocks of proteins vital to the growth and reproduction of bacteria, these results provide an insight into the mechanism of bacterial inactivation by plasma.